Features of the pregnancy and delivery course, fetal and newborn status in women with COVID-19 - Beniuk, V.O.; Hychka, N.M.; Zabudskyi, O.V.; Fursa-Sovhyra, T.M.; Kovaliuk, T.V.; Oleshko, V.F.; Chebotarova, A.S. (Reproduktivnaâ èndokrinologiâ, 2021)
Research objective. To evaluate the features of pregnancy and delivery course, fetal and newborn status in women with confirmed COVID-19.Materials and methods. A retrospective clinical and statistical analysis of 106 pregnancy and delivery case histories and medical records of newborn from women with a gestation period of 22–41 weeks with a confirmed diagnosis of COVID-19 was carried out. Women were treated and delivered on the temporarily converted beds for providing obstetric care to pregnant women, women in labor and postpartum women with suspected and infected COVID-19 and gynecological patients of Municipal Non-Profit Enterprise “Kyiv City Maternity Hospital No. 3” from September 2020 to May 2021.Results. Delivery took place in 48 women. Women with A (II) blood group were significantly predominant – 51 (48.1%) and rhesus-positive factor – 85 (80.2%) (p < 0.05). One third of pregnant women sought medical help on their own – 34 (32.1%). 94 (88.7%) women had a positive PCR test, in 6 (11.3%) cases the diagnosis was confirmed by a rapid test in the admission department; in 6 (11.3%) cases the test results were negative. The leading complaints when pregnant women were hospitalized were fever, cough and fatigue in 85 (80.2%), 90 (84.9%) and 73 (68.9%) pregnant women respectively (p < 0.05). Almost every third woman (39, 36.8%) had a subfebrile temperature – 37.0–37.5 oC. In 15 (14.1%) patients the temperature was 38.0–38.5 oC, in 6 (5.7%) patients over 38.5 oC. At the lung ultrasound the signs of bilateral and polysegmental pneumonia were diagnosed in 44 (53.6%) and 36 (43.9%) cases. Lower and upper lobe pneumonia was diagnosed in 20 (24.4%) pregnant women. Severe lung damage was detected in 29 (35.4%) pregnant women in the form of partial “hepatization” of lung tissue, pleural effusion in the form of black areas of various sizes in the pleural cavity.Conclusions. The main typical SARS CoV-2 complaints in hospitalized pregnant women were fever, cough, fatigue and shortness of breath at rest and during exercise. Such neurological manifestations of SARS CoV-2 as headache, anosmia were noted by almost every third pregnant woman, and parosmia and myalgia were noted by every fourth pregnant woman. The average level of C-reactive protein was above normal in 97.2% of women. Lung ultrasound allowed clearly identifying areas of damage and determining the degree of lung tissue damage. Цель исследования. Оценить особенности течения беременности, родов, состояния плода и новорожденного у женщин с подтвержденным COVID-19.Материалы и методы. Проведен ретроспективный клинико-статистический анализ 106 историй беременности и родов женщин (и медицинских карт их новорожденных) в сроке гестации 22–41 недели, которые находились на лечении и родоразрешении на временно перепрофилированных койках для оказания акушерской помощи беременным, роженицам и родильницам с подозрением и инфицированных COVID-19 и гинекологических больных КНП «Киевский городской родильный дом» № 3 с сентября 2020 г. по май 2021 г. с подтвержденным диагнозом COVID-19.Результаты. Среди обследованных достоверно преобладали женщины с А (II) группой крови (51, 48,1%) и резус-положительным фактором (85, 80,2%) (р < 0,05). Треть беременных обратилась за медицинской помощью самостоятельно – 34 (32,1%). У 94 (88,7%) женщин был положительный ПЦР-тест, в 6 (11,3%) случаях диагноз подтвержден экспресс-тестом в приемном отделении, в 6 (11,3%) случаях результаты тестов оказались отрицательными. Ведущими жалобами при поступлении беременных в стационар были лихорадка, кашель и утомляемость, которые беспокоили 85 (80,2%), 90 (84,9%) и 73 (68,9%) женщин (р < 0,05). Практически у каждой третьей беременной (39, 36,8%) была субфебрильная температура тела – 37,0–37,5 оС. У 15 (14,1%) больных температура достигала 38,0–38,5 оС, у 6 (5,7%) – более 38,5 оС. В ходе УЗИ легких признаки двусторонней и полисегментарной пневмонии выявлены в 44 (53,6%) и 36 (43,9%) случаях соответственно, нижне- и верхнедолевая пневмония – в 20 (24,4%). У 29 (35,4%) беременных обнаружено тяжелое поражение легких в виде частичной «гепатизации» легочной ткани, плеврального выпота в виде черных участков различного размера в плевральной полости.Выводы. Основными жалобами, характерными для SARS CoV-2, у госпитализированных беременных были лихорадка, кашель, утомляемость и одышка в покое и при физической нагрузке. Такие неврологические проявления SARS CoV-2, как головная боль, аносмия, отмечала практически каждая третья беременная, а паросмию и миалгию – каждая четвертая. У 97,2% женщин средний уровень С-реактивного белка превышал норму. УЗИ легких позволяло четко выявить участки поражения и определить степень поражения легочной ткани. Мета дослідження. Оцінити особливості перебігу вагітності, пологів, стану плода й новонародженого в жінок із підтвердженим COVID-19.Матеріали і методи. Проведено ретроспективний клініко-статистичний аналіз 106 історій вагітності та пологів жінок (і медичних карт їхніх новонароджених) на терміні гестації 22–41 тиждень, які перебували на лікуванні й розродженні на тимчасово перепрофільованих ліжках для надання акушерської допомоги вагітним, роділлям і породіллям із підозрою та інфікованих COVID-19 і гінекологічних хворих КНП «Київський міський пологовий будинок № 3» від вересня 2020 р. до травня 2021 р. із підтвердженим діагнозом COVID-19.Результати. Пологи відбулись у 48 жінок. Серед обстежених достовірно переважали жінки з А (ІІ) групою крові (51, 48,1%) і резус-позитивним фактором (85, 80,2%) (р < 0,05). Третина вагітних звернулися по медичну допомогу самостійно – 34 (32,1%). 94 (88,7%) жінок мали позитивний ПЛР-тест, у 6 (11,3%) випадках діагноз підтверджено експрес-тестом у приймальному відділенні, у 6 (11,3%) випадках результати тестів виявилися негативними. Провідними скаргами при надходженні вагітних до стаціонару були гарячка, кашель і втомлюваність, які турбували 85 (80,2%), 90 (84,9%) та 73 (68,9%) вагітних відповідно (р < 0,05). Практично кожна третя вагітна (39, 36,8%) мала субфебрильну температуру тіла – 37,0–37,5 оС. У 15 (14,1%) хворих температура сягала 38,0–38,5 оС, у 6 (5,7%) – понад 38,5 оС. Під час УЗД легень ознаки двобічної та полісегментарної пневмонії діагностовано в 44 (53,6%) і 36 (43,9%) випадках, нижньо- і верхньочасткова пневмонія – у 20 (24,4%). У 29 (35,4%) вагітних виявлено тяжке ураження легень у вигляді часткової «гепатизації» легеневої тканини, плеврального випоту у вигляді чорних ділянок різного розміру в плевральній порожнині.Висновки. Основними скаргами, характерними для SARS CoV-2, у госпіталізованих вагітних були гарячка, кашель, втомлюваність і задишка в стані спокою та при фізичному навантаженні. Такі неврологічні вияви SARS CoV-2, як головний біль, аносмія, мала практично кожна третя вагітна, а паросмію та міалгію – кожна четверта. У 97,2% жінок середній рівень С-реактивного білка перевищував норму. УЗД легень дозволяло чітко виявити ділянки ураження й визначити ступінь ураження легеневої тканини.